Cloud Point Extraction and Determination of Silver Ion in Real Sample using Bis((1H-benzo[d ]imidazol-2yl)methyl)sulfane - Farshid Ahmadi; Khodabakhsh Niknam; Ebrahim Niknam; Saeid Delavari; Azadeh Khanmohammadi (E-Journal of Chemistry)
Bis((1H-benzo[d]imidazol-2yl)methyl)sulfane (BHIS) was used as a complexing agent in cloud point extraction for the first time and applied for selective pre-concentration of trace amounts of silver. The method is based on the extraction of silver at pH 8.0 by using non-ionic surfactant T-X114 and bis((1H-benzo[d]imidazol-2yl)methyl)sulfane as a chelating agent. The adopted concentrations for BHIS, Triton X-114 and HNO3, bath temperature, centrifuge rate and time were optimized. Detection limits (3SDb/m) of 1.7 along with enrichment factor of 39 for silver ion was achieved. The high efficiency of cloud point extraction to carry out the determination of analytes in complex matrices was demonstrated. The proposed method was successfully applied to the ultra-trace determination of silver in real samples.